Արտամետ քաղաքի գրչության կենտրոնը - Թումանյան, Լուսինե
The town of Artamet housed one of the scriptoria of the Vaspurakan province. Many Armenian manuscripts were copied here at different times. The earliest manuscript known to us, dating back to 1369 is Grigor Narekats‘i’s Book of Lamentations (Ms M5883), copied by the monk Step‘annos. This manuscript is unique, as the book is divided into three parts: chapters 1-34, chapters 35-74, chapters 75-95. Other manuscripts from Artamet have also reached us. In 1569, a priest named Nikoghayos copied the Four Gospels (Ms M5490). There is information about a manuscript, copied by priest Karapet in 1605 in Artamet. The next known manuscript from Artamet is a Horologion dated to the 17th century (Ms M5533). The scribe of this manuscript was a priest named David. The scribe of manuscripts M4726 and M5381 is called David Artamets‘i; we conlude that he is the same priest David. Manuscript Ms M5381 is a copy of the Four Gospels dating to 1682, and manuscript M4726 is a Homilary. In 1655, a scribe named Khachatur copied a Hymnal (Sharaknots‘) at Artamet, the fate of which is unknown today. Of course, other manuscripts were also copied in Artamet, which have not reached us due to various disasters and wars. Один из скрипториев провинции Васпуракан находился в городе Артамет. Здесь в разное время было создано множество армянских рукописей. Самая ранняя известная нам рукопись датируется 1369 годом. Это «Книга скорбных песнопений» (называемая также «Молитвенник») Григора Нарекаци (Матенадаран, рук. 5883), переписанная монахом Степанносом. Эта рукопись уникальна, так как книга разделена в ней на три части: главы 1-34, главы 35-74, главы 75-95. До нас дошли и другие рукописи из Артамета. В 1569 году священник Николай переписал Четвероевангелие (Матенадаран, рук. 5490). Есть сведения о Евангелии, переписанном священником Карапетом в 1605 году в Артамете. Следующая известная рукопись из Артамета – Часослов, датированный XVII веком (Матенадаран, рук. М5533). Писец этой рукописи – священник Давид. Переписчиком рукописей Матенадарана 4726 и 5381 является Давид Арта- метци, которого, вероятно можно отождествить со священником Давидом. Рукопись М5381 – Четвероевангелие (переписано в 1682 году) а рукопись М4726 – Гомилиарий. В 1655 году писец Хачатур скопировал в Артамете Гимнарий (Шаракноц), судьба которого сегодня неизвестна. Естественно, в Артамете переписывались и другие рукописи, не дошедшие до нас из-за различных исторических катаклизмов.
Keywords: Ձեռագրական մշակույթ